PENYULUHAN DAN PELATIHAN PEMBUATAN MIKROORGANISME LOKAL (MOL) SEBAGAI PUPUK ORGANIK CAIR PADA MASYARAKAT PETANI DI DESA LUBUK BENTENG KECAMATAN BATHIN III KABUPATEN BUNGO - Effi Yudiawati; Setiono; Gusni Yelni; Subagiono; Hasnelly; Budi Prastia (Fakultas Pertania Universitas Muara Bungo, 2023)
Lubuk Benteng Village is one of the villages with the main commodity of rice plants. This community service activity was carried out in Lubuk Benteng Village, Bathin III District, Bungo Regency, Jambi Province. The purpose of this Community Service (PKM) activity is to provide counseling and training to farming communities on how to make Local Microorganisms (MOL) which can then be used as liquid organic fertilizer and as decomposer bodies in composting. The method applied in this activity is in the form of direct counseling and training in making MOL. The results of the assistance show that the farmers understand the knowledge about liquid organic fertilizer made from MOL and how to make it. MOL makes it easier for farmers to use organic and inexpensive liquid fertilizers so that the use of chemical fertilizers will be reduced. Keywords : Liquid Fertilizer, Organic, Microorganisms, MOL, waste.